A ANALYTICAL STUDY OF JAYPAL BEEJA (CROTON TIGLIUM LINN.) W.S.R. TO ITS SHODHANA PROCESS IN GOMUTRA AND GODUGDHA - Vinisha Giri*; Prafulla (AYUSHDHARA, 2018)
Jaypal beeja (Croton tiglium linn.), is classified under Upvisha Dravya (Semi poisonous drugs). In classical Ayurvedic pharmacopoeias it is advocated that Shodhana (purificatory procedures) of the Beeja (seeds) should be carried out before its internal administration. Though there are different Shodhana methods mentioned in Classics. In this study Godugdha and Gomutra and were used as media. They impact of Shodhana was evaluated by physico-chemical and chromatographical parameters. Chromatological evaluation of the media used (after purification) showed different Rf value. Among the 2 media used more Rf values showed in Godugdha media signifying more toxic removed from drug into media. Upon analyzing TLC, HPTLC and other parameter also Godugdha media has been proved significant purificatory media compared to Gomutra. The HPTLC data interpreted for major component of this plant is Crotonoside showing major spots in the TLC and HPTLC data. At 0.8 Rf rest of the component are in traces amount.